Reverse Osmosis (RO) Drinking Water Management as the Best Solution to Overcome the Clean Water Crisis in Pinang Island - Khairil, Dewi Fortuna; Insani, Munadia; Setiawan, Arif; Febryanti, Febryanti; Rabbi, Elfandra Fadhli; Barlian, Eri; Dewata, Indang; Syah, Nurhasan; Heldi, Heldi; Umar, Iswandi; Kamal, Eni (Science and Environmental Journal for Postgraduate, 2023)
Reverse Osmosis (RO) drinking water management can be the best solution to overcome the clean water crisis in Pulau Pinang. RO is a process that allows water to pass through a semi-permeable membrane and separates most of the dissolved salts, organic matter, bacteria, and other substances from the water to produce clean water. The use of the RO method in drinking water management is one of the best alternatives to overcome the clean water crisis, especially in the Pinang Island area with surface water sources that are not dominated by freshwater can ensure the availability of sustainable clean water. However, RO-based drinking water management is water demineralization, so further management is needed such as remineralization to meet mineral standards in drinking water.